Analysis of spinal muscular atrophy carrier screening results in 32,416 pregnant women and 7,231 prepregnant women - Zhou, Bing-bo; Chen, Xue; Zhang, Chuan; Wang, Yu-pei; Ma, Pan-pan; Hao, Sheng-ju; Hui, Ling; Bai, Yun-fei (Frontiers in Neurology, 2024)
Objectives Spinal muscular atrophy (SMA) is an autosomal recessive disease that is one of the most common in childhood neuromuscular disorders. Our screenings are more meaningful programs in preventing birth defects, providing a significant resource for healthcare professionals, genetic counselors, and policymakers involved in designing strategies to prevent and manage SMA. Method We screened 39,647 participants from 2020 to the present by quantitative real-time PCR, including 7,231 pre-pregnancy participants and 32,416 pregnancy participants, to detect the presence of SMN1 gene EX7 and EX8 deletion in the DNA samples provided by the subjects. To validate the accuracy of our findings, we also utilized the Multiplex Ligation-dependent Probe Amplification (MLPA) to confirm the reliability of screening results obtained by quantitative real-time PCR. Result Among the 39,647 participants who were screened, 726 participants were the carriers of SMN1. The overall carrier rate was calculated to be 1.83% (95% confidence interval: 0.86–2.8%). After undergoing screening, a total of 592 pregnancy carriers were provided with genetic counseling and only 503 of their spouses (84.97, 95% confidence interval: 82.09–87.85%) voluntarily underwent SMA screening. Conclusion This study provides crucial insights into the prevalence and distribution of SMA carriers among the female population. The identification of 726 asymptomatic carriers highlights the necessity of comprehensive screening programs to identify at-risk individuals and ensure appropriate interventions are in place to minimize the impact of SMA-related conditions.